Analyzing Potential Misuse of Notarial and PPAT Deeds for Covert Gratification - Budiman, Angela Benita; Birra, Azka Nisa Al; Oxanifer; Taufiqurokhman; Watriningsih (Universitas prof. Dr. Moestopo (Beragama), 2026)
This study aims to examine the potential misuse of notarial and Land Deed Official (PPAT) deeds as formal legal instruments that may operate as concealed channels for illicit gratuities, while also proposing preventive measures to mitigate associated risks. The research employs a normative-empirical approach by integrating statutory analysis with a conceptual framework, focusing on the Law on Notary Office, anti-corruption regulations, and patterns of disguised gratification practices involving authentic deeds. The findings demonstrate that covert gratuities can be facilitated through various notarial documents, particularly sale and purchase agreements, loan contracts, and grant deeds, which may be deliberately structured to obscure unlawful benefits. The study concludes that preventing such misuse requires strengthening professional diligence and regulatory compliance. First, notaries and PPAT officials must rigorously verify the factual accuracy of information provided by the parties and ensure its proper legal formulation, guided by principles of transparency, prudence, and accountability. Second, the consistent implementation of customer due diligence and accurate identification procedures is essential to minimize abuse. These measures are crucial for enhancing legal certainty and maintaining public trust in notarial institutions.